Least-cost decarbonization pathways for electricity generation in Finland: A convex quantile regression approach - Natalia Kuosmanen; Timo Kuosmanen; Terhi Maczulskij; Xun Zhou (The Research Institute of the Finnish Economy (ETLA), 2024)
This study investigates the least-cost decarbonization pathways in the Finnish electricity generation industry in order to achieve the national carbon neutrality goal by 2035. Various abatement measures, such as downscaling production, capital investment, increasing labor and intermediate inputs are considered. The marginal abatement costs (MACs) of greenhouse gas emissions are estimated using the convex quantile regression method and applied to unique register-based firm-level greenhouse gas emission data merged with financial statement data. We adjust the MAC estimates for the sample selection bias caused by zero-emission firms by applying the two-stage Heckman correction. Our empirical findings reveal that the median MAC ranges from 0.1 to 3.5 euros per tonne of CO2 equivalent. The projected economic cost of a 90% reduction in emissions is 62 million euros, while the estimated cost of achieving zero emissions is 83 million euros.
Keywords: O44; Q43; Q51; Q52; Q54; 330; Abatement cost; Convex quantile regression; Forward-looking assessment; Climate policy; Decarbonization pathways